Efectividad del programa educativo “trascendiendo con amor” en el nivel de agresividad en escolares – Pacanguilla - Campos Veintemilla, Laura Patricia (2019)
The present investigation of quantitative type, pre experimental of transversal cut, was realized in the Educational Institution N °80403 Cristo Rey in the center of Pacanguilla, Pacanga district, Chepén province, La Libertad, during the 2018, with the purpose of determining the Effectiveness of the Educational Program "Transcending with Love" in the level of aggressiveness in school children of 8 and 9 years of age. The sample consisted of 30 school children who met the inclusion criteria. For data collection the Aggression Questionnaire (Vs. Española) of Andreu, Peña and Graña (2002) was used, the information obtained was processed in the SPSS 25 and analyzed by means of the statistical test of Marginal Homogeneity. The results are presented in tables of distribution of one-dimensional frequencies, after the analysis the following conclusions were reached: After the application of the educational program, the students who presented a high level of aggressiveness, decreased by 50 percent; that is, the educational program "Transcending with love" was effective.